KONSTRUKSI HUKUM EKSEKUSI ATAS PUTUSAN ARBITRASE YANG MEMBERIKAN KEPASTIAN DAN KEADILAN (STUDI KASUS PUTUSAN NO. 203/PDT.G/2020/PN.JKT.PST) - Anisa Nurul Qoumy, (2023)
In this research, the author examines how the legal construction of the execution of an award that has been decided by an arbitral institution in norms and practices. In Law no. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, the Arbitration Award is final and binding but in practice the Arbitration Award can be submitted for annulment and resistance to confiscation of execution which ends in appeals, cassation and judicial review as happened in case No. 203/Pdt.G/2022/PN.Jkt.Pst. With the opening of these other efforts, the Arbitration Award will not truly be final and binding. So that this results in legal uncertainty and legal justice. Meanwhile, business actors need legal certainty and legal justice in the execution of the Arbitration Award. The research method in this study uses normative juridical. The results of the study of the first problem formulation show that the Decision on Case No. 203/Pdt.G/2022/PN.Jkt.Pst is one example that the legal construction of the execution of Arbitration Awards in Indonesia has not provided a sense of legal certainty and legal justice for the parties because the Author finds legal uncertainty and injustice in the Decision. The results of the study of the second problem formulation show that the law on the execution of Arbitral Awards in Indonesia has not provided a sense of legal certainty and legal justice for the parties because the law on the execution of Arbitral Awards has not been regulated in detail in Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. So that the essence of the Arbitration Award is not in line with the law of execution and execution in Indonesia.